2017
DOI: 10.1159/000480471
|View full text |Cite
|
Sign up to set email alerts
|

Oxymatrine Ameliorates Doxorubicin-Induced Cardiotoxicity in Rats

Abstract: Background/Aims: Doxorubicin-induced cardiac toxicity has been a major concern of oncologists and is considered the main restriction on its clinical application. Oxymatrine has shown potent anti-cancer, anti-fibrosis, and anti-oxidative effects. Recently, it has been reported that oxymatrine is protective against some cardiovascular diseases. In this study, we aimed to investigate the effects of oxymatrine on doxorubicin-induced cardiotoxicity in rat hearts and H9c2 cells. Methods: Creatine Kinase - MB (CK-MB)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
48
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(60 citation statements)
references
References 32 publications
5
48
1
1
Order By: Relevance
“…Several rats were exposed to DOX (3 mg/kg, Sigma-Aldrich) by intraperitoneal injections (single dose of DOX every another day for total three injections) [ 17 ]. Recombinant klotho protein (0.01 mg/kg, R&D) was administrated to rats by intraperitoneal injections every another day for total two injections [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several rats were exposed to DOX (3 mg/kg, Sigma-Aldrich) by intraperitoneal injections (single dose of DOX every another day for total three injections) [ 17 ]. Recombinant klotho protein (0.01 mg/kg, R&D) was administrated to rats by intraperitoneal injections every another day for total two injections [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…Then the cells were maintained in MEM containing bovine serum albumin (0.1 mg/mL, Gibco), L-glutamine (2 mmol/L, Gibco) and antibiotics mix (Sigma-Aldrich) in a cell incubator providing humidified environment, constant temperature at 37°C and fresh air (5% CO 2 ). DOX (1 μmol/L for 24 hours) [ 17 ], klotho (400 pmol/L, four hours prior to DOX exposure) [ 23 ], specific MAPKs inhibitors and specific small interference RNAs (siRNA) against genes MAPKs were used to incubate the isolated myocytes. Control cells were incubated with MEM.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, it is proved by Chen et al that the anti-hypertensive active of Radix Paeoniae Alba extract may be related to its effect on regulating serum nitric oxide and endothelin levels [38]. Oxymatrine, one of the principle components of Radix Sophorae Flavescentis, was demonstrated in vitro and in vivo by Zhang et al that may be a promising cardioprotective agent in part through inhibition of cardiac apoptosis and oxidative stress [39].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that OXY preprocessing deduced level of ROS production in renal tissue caused by ischemia/reperfusion and activated serum antioxidant enzyme activities. Oxymatrine also ameliorated pathological damage in myocardial tissue induced by doxorubicin with anti-oxidative and anti-inflammatory effects [23,24]. Furthermore, oxymatrine has been shown to improve microcirculation and liver function [24].…”
Section: Histological Examinationmentioning
confidence: 97%
“…Oxymatrine also ameliorated pathological damage in myocardial tissue induced by doxorubicin with anti-oxidative and anti-inflammatory effects [23,24]. Furthermore, oxymatrine has been shown to improve microcirculation and liver function [24]. Previous studies identified that the mitochondrial dysfunction [27,28], apoptosis/necrosis [29,30] and inflammation [31] are also included in gentamicin-induced kidney injury in rats and human renal proximal tubular cells (HKC).…”
Section: Histological Examinationmentioning
confidence: 99%